Using the morphology of the hominoid distal fibula to interpret arboreality in Australopithecus afarensis. Issue 85 (August 2015) - Marchi, Damiano
Abstract: The fibula has rarely been considered in anthropological studies. However differences in morphology — and inferred function — of the fibula between human and non-human apes have been noted in the past and related to differences in locomotor behavior. Recent studies have pointed out the correlation between diaphyseal rigidity of the fibula and tibia and locomotor behavior in living hominids, and its possible application for inferring early hominin locomotor behavior. The problem with the application of the method proposed in these studies is the extreme rarity of associated early hominin fibula and tibia. Additionally, previous studies investigating morphological traits of fibulotalar articular facets to infer the degree of arboreality in fossil australopiths were often qualitative. In the present study, articular measurements of the distal fibula of living great apes and humans ( Pongo, Gorilla, Pan and Homo ) are quantified and compared to Australopithecus afarensis distal fibulae. Quantitative analysis is carried out for articular areas and breadths of the fibulotalar articular facets, for the angles formed by the fibulotalar articular facets and the longitudinal axis of the fibula, and for the angle between the proximal fibulotalar articular facet and the subcutaneous triangular area. Results show that the fibula of A. afarensis bears some traits consistent with modern terrestrial bipedalism, like a more laterally facing lateral malleolus, in association with more ape-like traits, like the smaller distal fibulotalar articular facet area and the more inferiorly oriented fibulotalar articular facets, consistent with A. afarensis being a terrestrial hominin adapted for some form of arboreality.